Enzymatic activity of the human 1-acylglycerol-3-phosphate-O-acyltransferase isoform 11: upregulated in breast and cervical cancers[S] - Anil K. Agarwal; Abhimanyu Garg (Journal of Lipid Research, 2010)
The conversion of lysophosphatidic acid (LPA) to phosphatidic acid is carried out by the microsomal enzymes 1-acylglycerol-3-phosphate-O-acyltransferases (AGPATs). These enzymes are specific for acylating LPA at the sn-2 (carbon 2) position on the glycerol backbone and are important, because they provide substrates for the synthesis of phospholipids and triglycerides. At least, mutations in one isoform, AGPAT2, cause near complete loss of adipose tissue in humans. We cloned a cDNA predicted to be an AGPAT isoform, AGPAT11. This cDNA has been recently identified also as lysophosphatidylcholine acyltransferase 2 (LPCAT2) and lyso platelet-activating factor acetyltransferase. When AGPAT11/LPCAT2/lyso platelet-activating factor acetyltransferase cDNA was expressed in CHO and HeLa cells, the protein product localized to the endoplasmic reticulum. In vitro enzymatic activity using lysates of Human Embryonic Kidney-293 cells infected with recombinant AGPAT11/LPCAT2/lyso platelet-activating factor-acetyltransferase cDNA adenovirus show that the protein has an AGPAT activity but lacks glycerol-3-phosphate acyltransferase enzymatic activity. The AGPAT11 efficiently uses C18:1 LPA as acyl acceptor and C18:1 fatty acid as an acyl donor. Thus, it has similar substrate specificities for LPA and acyl-CoA as shown for AGPAT9 and 10. Expression of AGPAT11 mRNA was significantly upregulated in human breast, cervical, and colorectal cancer tissues, indicating its adjuvant role in the progression of these cancers. Our enzymatic assays strongly suggest that the cDNA previously identified as LPCAT2/lyso platelet-activating factor-acetyltransferase cDNA has AGPAT activity and thus we prefer to identify this clone as AGPAT11 as well.